VARIASI KOSENTRASI EKSTRAK ETANOL KULIT BUAH MANGGA HARUM MANIS (Mangifera indica L var. arum manis) TERHADAP FORMULA SEDIAAN GEL HAND SANITIZER SEBAGAI ANTIBAKTERI - Yuska Noviyanty; Hepiyansori Hepiyansori; Annis Annis (Denta Journal Kedokteran Gigi, 2022)
One of the medicinal plants that can be used as a source of natural medicine is mango (Mangifera indica L.) because it contains secondary metabolite compounds, mango plants contain many benefits both at the root, skin, leaves, fruits and seeds. Mango skin contains important active compounds such as phenolic compounds, carotenoids, flavonoids and anthocyanins. Sweet Arum mango skin has antibacterial activity. The extraction method used is maceration with 96% ethanol solvent. The formulation was prepared using Na.CMC as a gelling agent with a concentration of 2%, 4%, 8%. The evaluation test of mango skin extract hand sanitazer preparation includes organoleptic test, homogeneity test, pH test, spreadability test, sticking test, irritation test and antibacterial test. The results showed that the physical properties of the gel preparations had an influence on the physical properties of the mango skin extract gel (Mangifera indica L). Based on the antibacterial activity test the concentration of 2%, 4%, 8% which most strongly shows the antibacterial activity at a concentration of 8% with an average value of 18.28 mm.